Uma reflexão sobre a qualidade de vida nos ambientes urbanos: parques e academias ao ar livre no municipio de Curitiba - Maranho, Mariana Ciminelli (2013)
The quality of life, while guiding by public policies, comes gradually acquiring expression since the 19th century, and can be retract in the changes of strategies for urban planning. More recently the quality of life has been understood from the perspective of their intimate relationship with the adoption of healthy lifestyles, being many times, connected to the deployment of public spaces and equipment for sports and leisure. Curitiba, specifically, has a significant number of spaces and public facilities for sports and leisure activities, such as parks and academies to open air, installed with greater emphasis from the year 1970, placed by city marketing as a way to achieve the quality of life. Search-if reflect, in this study, about the relationships that are established between the urban growth of the last few decades and the concerns of authorities and specialists in equipping the cities with tools, committed to the quality of life, taking as a reference the investments in public space of the city of Curitiba, from the year 1970, highlighting, among these investments, the deployment of the parks, and more recently, academies to open air. It is understood that public policies associated with the quality of life perpass the different forms as the society organizes itself in space, being shaped and conditioned to the interaction of subjects.